Hydrogenolytic depolymerization of procyanidin polymers from hi-tannin sorghum bran. (1st December 2015) - Li, Zheng; Zeng, Jijiao; Tong, Zhaohui; Qi, Yajing; Gu, Liwei
Highlights: Procyanidin polymers were extracted from hi-tannin sorghum bran. Hydrogenolysis was applied to depolymerize procyanidin polymers into oligomers. Hydrogenolysis conditions on depolymerization of polymers were investigated. Mechanism of depolymerization of polymers into oligomers was proposed. Abstract: Depolymerization of procyanidin polymers into oligomers enhances their bioavailability and bioactivity because oligomers are bioavailable. Hydrogenolysis was applied in this study to depolymerize hi-tannin sorghum bran procyanidin polymers into oligomers. The yield and composition of oligomers under different hydrogenolysis conditions was investigated. Results showed that raising temperature from 50 to 100 °C significantly increased total yield of oligomers. Higher temperatures (150 and 200 °C) produced monomers with lower yield. The highest yield of oligomers (38.8%) was obtained using 1 MPa hydrogen whereas 3 MPa hydrogen in reaction vessel decreased yield. Total yield of oligomers reached the highest at 1–3 h and then decreased with prolonged reaction time. Yield increased with palladium-on-carbon (Pd/C, a catalyst) amount from 0.5 to 3 mg and plateaued with Pd/C amount from 3 to 10 mg. The maximum yield of produced oligomers was achieved under 100 °C, 1 MPa hydrogen pressure, 1–3 h, and 3–10 mg Pd/C.